A numerical model for snow drifting simulations on flat roofs using Lagrangian approach. Issue 222 (March 2022) - Liu, Zhenbiao; Zhou, Xuanyi; Gu, Ming
Abstract: A numerical model based on Lagrangian description is developed in this study to predict wind-induced snow drifting on flat roofs, which fully considers the key physical processes of snow particle saltation. A scaled experiment of snow redistributions on the model roof was carried out in the wind tunnel for the verification and evaluation of different numerical methods selected from related literature. The optimal model is determined by comparing the predicted transport rate on the roof with estimations from empirical formulas and by comparing simulated snow distributions with experimental data. Characteristics of the saltation layer above the flat roof surface are then presented in detail based on the developed model. The rebound particles account for approximately 60% of the total transported particles above the roof, indicating the dominant role of rebound in the lift-off process for saltating snow particles. The developing snow transport along the roof span leads to the increase of surface erosion flux caused by the splash entrainment with downwind distance. The splash entrainment could thus contribute considerably to unsaturated snow transport on the flat roof, which is also found to be influenced by the approaching wind velocity and threshold friction velocity to varying degrees. Highlights: A numerical model is developed using the Lagrangian approach to investigate the mechanisms of snow drifting on flat roofs. A scaled experiment of snow redistributions on flat roof is conducted in the wind tunnel to evaluate the simulated results. Characteristics of the saltation layer above the flat roof are presented based on the developed model. The role of splash entrainment and its contribution to unsaturated snow transport on flat roofs are preliminarily explored.